1986
DOI: 10.1523/jneurosci.06-10-03024.1986
|View full text |Cite
|
Sign up to set email alerts
|

Activation of substantia nigra neurons: role in the propagation of seizures in kindled rats

Abstract: The substantia nigra (SN) is crucial to the propagation of seizures in kindled rats and in other experimental seizure models. However, the mechanisms by which the SN acts to facilitate the propagation of seizures are unknown. To investigate these mechanisms we quantified the activity of SN neurons during seizures in kindled and naive rats in a paralyzed, ventilated state and examined the relationship between activity of neurons in the SN and the seizure-facilitating action of this structure. Our principal find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 21 publications
4
33
1
Order By: Relevance
“…This has been demonstrated by the absence of c-fos expression in pars reticulata of substantia nigra (Labiner et al, 1993) following a kindled seizure. Unit recordings of pars reticulata neurons of substantia nigra during a class 5 kindled seizure demonstrate burst-firing (Bonhaus et al, 1986;Bonhaus et al, 1991) yet no evidence of seizure-evoked IEG expression was detected here or in our previous work (Labiner et al, 1993).…”
Section: Constitutive Expression Of Ieg Mrnas 28 D After Angular Bundcontrasting
confidence: 51%
“…This has been demonstrated by the absence of c-fos expression in pars reticulata of substantia nigra (Labiner et al, 1993) following a kindled seizure. Unit recordings of pars reticulata neurons of substantia nigra during a class 5 kindled seizure demonstrate burst-firing (Bonhaus et al, 1986;Bonhaus et al, 1991) yet no evidence of seizure-evoked IEG expression was detected here or in our previous work (Labiner et al, 1993).…”
Section: Constitutive Expression Of Ieg Mrnas 28 D After Angular Bundcontrasting
confidence: 51%
“…The activity of SNr neurons in particular has been positively correlated with seizure activity and generalization (Bonhaus et al, 1986;Deransart et al, 2003). It is also established that suppressing the activity of these neurons can be anticonvulsant (Iadarola and Gale, 1982), although this effect depends on the site of antagonist injection and also on animal age (Velíšková and Moshé, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent seizure stages are reached with equal number of stimulations in both groups. Several studies indicated that the progression of kindling from limbic sites involves the recruitment of a paleocortical network involving pirifonn, insular, and perirhinal cortices (20)(21)(22)(23) with the eventual propagation to basal ganglia and other subcortical structures (24,25) and eventually the brainstem (18,26). The development of kindling is different in immature rats compared with adults.…”
Section: Discussionmentioning
confidence: 99%